The Race Paradox in Mental Health Among Older Adults in the United States: Examining Social Participation as a Mechanism - Fei Wang; Shandra Forrest-Bank; Yifan Lou; Namrata Mukherjee; Yejin Heo (Social Sciences)
The race paradox in mental health refers to the phenomenon in which African Americans often demonstrate mental health outcomes that are comparable to or more favorable than those of non-Hispanic Whites, despite systemic socioeconomic disadvantage and disproportionate exposure to chronic stressors. Few studies have examined the mechanisms underlying this race paradox among older adults, and even fewer have explored the role of social participation. This study aims to examine whether social participation mediates the relationship between race and mental health. Longitudinal data were drawn from the National Social Life, Health, and Aging study Waves 1–3 (N = 1292). Race was dichotomized as African American and non-Hispanic White. Three types of social participation were assessed: volunteering, participating in organized groups, and attending religious services. Depressive symptoms were assessed as the mental health outcome. Path analyses were conducted to examine the aim. Results indicate that being African Americans predicted increased levels of religious attendance, which in turn, decreased the levels of depressive symptoms. Religious attendance is an underlying mechanism partially explaining the race paradox in mental health, and a modifiable factor that mitigates depressive symptoms. Culturally sensitive interventions promoting social participation are warranted.